TAYM-MENEDJMENT UMUMTA’LIM MAKTABLARINI BOSHQARISH SAMARADORLIGINI OSHIRISH VOSITASI SIFATIDA - Bekniyazov, B.S. (SCIENCE and SOCIETY, 2024)
This article analyzes the characteristics, types and directions, methods and levels of time management technology. The possibility of using time management technology is substantiated in the educational process.